Tell the Bosses We're Coming A New Action Plan for Workers in the Twenty-First Century. - Richman, Shaun (Monthly Review Press, 2020)
"Shaun Richman explains how important it is to bring labor unions back from the edge of institutional annihilation. Based on historical research and legal analysis, as well as his own experience as a union organizing director, Richman lays out an action plan for U.S. workers in the twenty-first century by which we can internalize the concept that workers are equal human beings, entitled to health care, dignity, job security-and definitely, the right to strike"--